Analisis Pemasaran Pinang Iris Di Nagari Bukik Sikumpa Kecamatan Lareh Sago Halaban Kabupaten Lima Puluh Kota - Winarni, Intan Permata; Afrizal, Roni; Silfia, Silfia (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
This pinang iris is a young betel nut that is easily peeled and sliced in the shape of a coin and dried, which is then marketed outside the province, namely to Papua, NTT, Kupang and other eastern parts of Indonesia. Good for the economic development of the community because of it’s sales. The price is higher than other processed betel nuts. This study aims to determine (1) identify marketing channels and the functions performed by pinang iris marketing institutions, (2) analyze the efficiency of pinang iris marketing using the marketing margin value and the share received by farmers (farmer's share) in the marketing of pinang iris. pinang iris people by using the purposive sampling method. Analysis of the data used is descriptive quantitative analysis. Based on the research that has been done, it can be concluded that: (1) the marketing channels of pinang iris in Nagari Bukik Sikumpa has 3 marketing channel patterns, namely, channel I of 62,50% which starts from Producers à collector traders à wholesalers in the province à Wholesalers outside the province, channel II is 21,88% starting from Producers à wholesalers within the province à wholesalers outside province, channel III amounted to 15,63% starting from Producers à wholesalers outside the province. (2) the functions performed by each marketing agency for pinang iris, both for channel I, II, and III are relatively even and precise. The costs incurred for each activity are still within reasonable limits. The three marketing channels of pinang iris, judging from the margins and farmer’s share, are relatively efficient. The most efficient marketing channel II margin value, with a value of Rp34.571,71 and from the farmer’s share the most efficient is in marketing channel III of 100%.